Question
upstudy study bank question image url

The function \( f(x)=\frac{5 x+7}{x-9} \) is one-to-0ne, a. Find an equation for \( f^{-1}(x) \), the inverse function, b. Verify that your equation is correct by showing that \( f\left(f^{-1}(x)\right)=x \) and \( f^{-1}(f(x))=x \). a. Select the correct choice below and fill in the answer box(es) to complete your choice, (Simplify your answers, Use integers or fractions for any numbers in the expression.) A. \( f^{-1}(x)= \) \( \square \) , for all \( x \) B. \( f^{-1}(x)=\frac{9 x+7}{x-5} \), for \( x \neq 5 \) c. \( f^{-1}(x)= \) \( \square \) , for \( x \geq \) \( \square \) D. \( f^{-1}(x)= \) \( \square \) , for \( x \leq \) \( \square \) b. Verify that the equation is correct. (Simplify your answers, Use integers or fractions for any numbers in the expression.) \[ \begin{array}{rlrlrl} f\left(f^{-1}(x)\right) & \equiv f(\square) & \text { and } & f^{-1}(f(x)) & \equiv f^{1}(\square) & \\ & \equiv \square & & \equiv \square & & \text { Substitute. } \\ & & & \text { Simplify. } \end{array} \]

Ask by Martinez Griffin. in the United States
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a. The inverse function is: \[ f^{-1}(x) = \frac{9x + 7}{x - 5}, \text{ for } x \neq 5 \] b. Verification: \[ f\left(f^{-1}(x)\right) = x \text{ and } f^{-1}(f(x)) = x \]

Solution

To solve the problem, we will follow the steps outlined: ### Part a: Find the inverse function \( f^{-1}(x) \) 1. **Start with the function**: \[ f(x) = \frac{5x + 7}{x - 9} \] 2. **Replace \( f(x) \) with \( y \)**: \[ y = \frac{5x + 7}{x - 9} \] 3. **Swap \( x \) and \( y \)** to find the inverse: \[ x = \frac{5y + 7}{y - 9} \] 4. **Multiply both sides by \( y - 9 \)** to eliminate the fraction: \[ x(y - 9) = 5y + 7 \] 5. **Distribute \( x \)**: \[ xy - 9x = 5y + 7 \] 6. **Rearrange the equation to isolate terms involving \( y \)**: \[ xy - 5y = 9x + 7 \] 7. **Factor out \( y \)**: \[ y(x - 5) = 9x + 7 \] 8. **Solve for \( y \)**: \[ y = \frac{9x + 7}{x - 5} \] Thus, the inverse function is: \[ f^{-1}(x) = \frac{9x + 7}{x - 5} \] ### Part b: Verify the inverse function 1. **Verify \( f(f^{-1}(x)) = x \)**: \[ f(f^{-1}(x)) = f\left(\frac{9x + 7}{x - 5}\right) \] Substitute \( \frac{9x + 7}{x - 5} \) into \( f(x) \): \[ f\left(\frac{9x + 7}{x - 5}\right) = \frac{5\left(\frac{9x + 7}{x - 5}\right) + 7}{\left(\frac{9x + 7}{x - 5}\right) - 9} \] Simplifying the numerator: \[ 5\left(\frac{9x + 7}{x - 5}\right) + 7 = \frac{45x + 35}{x - 5} + \frac{7(x - 5)}{x - 5} = \frac{45x + 35 + 7x - 35}{x - 5} = \frac{52x}{x - 5} \] Simplifying the denominator: \[ \left(\frac{9x + 7}{x - 5}\right) - 9 = \frac{9x + 7 - 9(x - 5)}{x - 5} = \frac{9x + 7 - 9x + 45}{x - 5} = \frac{52}{x - 5} \] Therefore: \[ f(f^{-1}(x)) = \frac{\frac{52x}{x - 5}}{\frac{52}{x - 5}} = x \] 2. **Verify \( f^{-1}(f(x)) = x \)**: \[ f^{-1}(f(x)) = f^{-1}\left(\frac{5x + 7}{x - 9}\right) \] Substitute \( \frac{5x + 7}{x - 9} \) into \( f^{-1}(x) \): \[ f^{-1}\left(\frac{5x + 7}{x - 9}\right) = \frac{9\left(\frac{5x + 7}{x - 9}\right) + 7}{\left(\frac{5x + 7}{x - 9}\right) - 5} \] Simplifying the numerator: \[ 9\left(\frac{5x + 7}{x - 9}\right) + 7 = \frac{45x + 63}{x - 9} + \frac{7(x - 9)}{x - 9} = \frac{45x + 63 + 7x - 63}{x - 9} = \frac{52x}{x - 9} \] Simplifying the denominator: \[ \left(\frac{5x + 7}{x - 9}\right) - 5 = \frac{5x + 7 - 5(x - 9)}{x - 9} = \frac{5x + 7 - 5x + 45}{x - 9} = \frac{52}{x - 9} \] Therefore: \[ f^{-1}(f(x)) = \frac{\frac{52x}{x - 9}}{\frac{52}{x - 9}} = x \] ### Final Answers a. The inverse function is: \[ f^{-1}(x) = \frac{9x + 7}{x - 5}, \text{ for } x \neq 5 \] b. Verification: \[ f\left(f^{-1}(x)\right) \equiv x \text{ and } f^{-1}(f(x)) \equiv x \]

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the inverse function \( f^{-1}(x) \), we start by replacing \( f(x) \) with \( y \): \[ y = \frac{5x + 7}{x - 9}. \] Now, we swap \( x \) and \( y \) to find the inverse: \[ x = \frac{5y + 7}{y - 9}. \] Next, we solve for \( y \): 1. Multiply both sides by \( y - 9 \): \[ x(y - 9) = 5y + 7. \] 2. Distributing the \( x \): \[ xy - 9x = 5y + 7. \] 3. Rearranging terms gives: \[ xy - 5y = 9x + 7. \] 4. Factoring out \( y \) from the left-hand side: \[ y(x - 5) = 9x + 7. \] 5. Finally, solving for \( y \), we get: \[ y = \frac{9x + 7}{x - 5}. \] Thus, the inverse function is: B. \( f^{-1}(x)=\frac{9 x+7}{x-5} \), for \( x \neq 5 \). Now, let’s verify that this equation is correct: To verify \( f(f^{-1}(x)) = x \): \[ f(f^{-1}(x)) = f\left(\frac{9x + 7}{x - 5}\right) = \frac{5\left(\frac{9x + 7}{x - 5}\right) + 7}{\left(\frac{9x + 7}{x - 5}\right) - 9}. \] Calculating the numerator: \[ = \frac{\frac{45x + 35}{x - 5} + 7}{\frac{9x + 7 - 9(x - 5)}{x - 5}} = \frac{\frac{45x + 35 + 7(x - 5)}{x-5}}{\frac{9x + 7 - 9x + 45}{x-5}} = \frac{\frac{45x + 35 + 7x - 35}{x-5}}{\frac{52}{x-5}} = \frac{52x}{52} = x. \] Now, to verify \( f^{-1}(f(x)) = x \): \[ f^{-1}(f(x)) = f^{-1}\left(\frac{5x + 7}{x - 9}\right) = \frac{9\left(\frac{5x + 7}{x - 9}\right) + 7}{\frac{5x + 7}{x - 9} - 5}. \] Calculating the numerator: \[ = \frac{\frac{45x + 63}{x - 9} + 7}{\frac{5x + 7 - 5(x - 9)}{x - 9}} = \frac{\frac{45x + 63 + 7(x - 9)}{x-9}}{\frac{5x + 7 - 5x + 45}{x-9}} = \frac{\frac{45x + 63 + 7x - 63}{x-9}}{\frac{52}{x-9}} = \frac{52x}{52} = x. \] Both \( f(f^{-1}(x)) = x \) and \( f^{-1}(f(x)) = x \) hold true, confirming our inverse function is valid.

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy